Measurement of the production cross-section of a single top quark in association with a W boson at 8 TeV with the ATLAS experiment - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Davygora, Yuriy; Djuvsland, Julia Isabell; Dunford, Monica; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; Jongmanns, Jan; et al. (Journal of high energy physics, 2016)
The cross-section for the production of a single top quark in association with a W boson in proton-proton collisions at s=8TeV$$ \sqrt{s}=8TeV $$is measured. The dataset corresponds to an integrated luminosity of 20.3 fb−1, collected by the ATLAS detector in 2012 at the Large Hadron Collider at CERN. Events containing two leptons and one central b-jet are selected. The W t signal is separated from the backgrounds using boosted decision trees, each of which combines a number of discriminating variables into one classifier. Production of W t events is observed with a significance of 7.7σ. The cross-section is extracted in a profile likelihood fit to the classifier output distributions. The W t cross-section, inclusive of decay modes, is measured to be 23.0 ± 1.3(stat.)− 3.5+ 3.2(syst.)±1.1(lumi.) pb. The measured cross-section is used to extract a value for the CKM matrix element |Vtb| of 1.01 ± 0.10 and a lower limit of 0.80 at the 95% confidence level. The cross-section for the production of a top quark and a W boson is also measured in a fiducial acceptance requiring two leptons with pT > 25 GeV and |η| < 2.5, one jet with pT > 20 GeV and |η| < 2.5, and ETmiss > 20 GeV, including both W t and top-quark pair events as signal. The measured value of the fiducial cross-section is 0.85 ± 0.01(stat.)− 0.07+ 0.07(syst.)±0.03(lumi.) pb.
*The ATLAS Collaboration: G. Aad, C.F. Anders, V. Andrei, A.E. Baas, O. Brandt, Y. Davygora, J.I. Djuvsland, M. Dunford, M.P. Geisler, M. Giulini, P. Hanke. J. Jongmanns, E.-E. Kluge, M. Kolb, M. Kretz, A. Kugel, V.S. Lang, M. Lisovyi, K. Meier, H. Meyer zu Theenhausen, D.I. Narrias Villar, M. Sahinsoy, S. Schaetzel, V. Scharf, S. Schmitt, A. Schoening, H.-C. Schultz-Coulon, D. Sosa, R. Stamen, P. Starovoitov, S. Suchek, M. Wessels [und sehr viele weitere Personen]
Gesehen am 29.06.2020